Implementasi Kebijakan Tentang Penyandang Disabilitas di Yayasan Wisma Cheshier dan Panti Sosial Bina Daksa Budi Bhakti Jakarta - Irsan Akhmad Abdulazis (Jurnal Ilmu Politik dan Pemerintahan, 2019)
This research aims to analyze the implementation of Permensos No. 7 of 2017 Concerning the Habilitation and Social Rehabilitation Standards for Persons with Disabilities at the PSBD Budi Bhakti and the Wisma Cheshier Jakarta. Qualitative approach with descriptive methods used in this research, as many as 15 informants with used purposive. Data collection techniques with interviews, observation and documentation. This Research used Miles and Huberman’s data analysis. The results of the study explained that, the implementation of Permensos No. 7 of 2017 in the PSBD is running quite well that is the communication indicators in terms of transmission, clarity and consistency has been going well, while the quality of human resources has met the standards set by the Ministry of Social Affairs but in terms of facilities there are still found some facilities that do not meet the standards, related to the disposition of employees already have a commitment, discipline and seriousness in implementing the policy. The bureaucratic structure is related to SOP that have met the standards set by the Ministry of Social Affairs and in terms of fragmentation aspects, the policy is socialized, starting from the level of the Ministry of Social Affairs down to the Social Service and then to the Social Institution. The results of the study explained that, the implementation of Permensos No. 7 of 2017 in the PSBD is running quite well that is the communication indicators in terms of transmission, clarity and consistency has been going well, while the quality of human resources has met the standards set by the Ministry of Social Affairs but in terms of facilities there are still found some facilities that do not meet the standards, related to the disposition of employees already have a commitment, discipline and seriousness in implementing the policy. The bureaucratic structure is related to SOPs that have met the standards set by the Ministry of Social Affairs and in terms of fragmentation aspects, the policy is socialized, starting from the level of the Ministry of Social Affairs down to the Social Service and then to the Social Institution.